ANALYSIS OF THE USE OF PHOTOELECTRIC PLANTS - Akhunov, K.Kh.; Khomidov, A.K. (Educational Research in Universal Sciences, 2023)
The article Secondly, in natural light conditions, the device can work autonomously, i.e. the proposed device is transformed into non-volatile and optically controlled. Thirdly, when preparing an industrial version of the BOZ, all the details of the device can be made in a thin-film form. This circumstance provides a basis for solving the problem of microminiaturization of an optoelectronic high-speed gate.